Therapeutic Antibodies to KIR3DL2 and Other Target Antigens on Cutaneous T-Cell Lymphomas - Schmitt, Christian; Marie-Cardine, Anne; Bensussan, Armand (Frontiers in Immunology, 2017)
KIR3DL2 is a member of the killer cell immunoglobulin-like receptor (KIR) family that was initially identified at the surface of natural killer (NK) cells. KIR3DL2, also known as CD158k, is expressed as a disulfide linked homodimer. Each chain is composed of three immunoglobulin-like domains and a long cytoplasmic tail containing two immunoreceptor tyrosine-based inhibitory motifs (ITIMs). Beside its expression on NK cells it is also found on rare circulating T lymphocytes, mainly CD8+. Although the KIR gene number varies between haplotype, KIR3DL2 is a framework gene present in all individuals. Together with the presence of genomic regulatory sequences unique to KIR3DL2, this suggests some particular functions for the derived protein in comparison with other KIR family members. Several ligands have been identified for KIR3DL2. As for other KIRs, binding to HLA class-I molecules is essential for NK development by promoting phenomena such as licensing or driving NK cell maturation. For KIR3DL2 this includes binding to HLA-A3 and -A11 and to the free heavy chain form of HLA-B27. In addition KIR3DL2 also binds to CpG oligonucleotides (ODN) and ensures their transport to endosomal TLR9 receptors that promote cell activation. These characteristics have implicated KIR3DL2 in several pathologies: ankylosing spondylitis and cutaneous T cell lymphomas such as Sézary syndrome, CD30+ cutaneous lymphoma and transformed mycosis fungoides. Consequently, a new generation of humanized monoclonal antibodies directed against KIR3DL2 has been helpful in the diagnosis, follow-up and treatment of these diseases. In addition, preliminary clinical studies of a novel targeted immunotherapy for cutaneous T cell lymphomas using the anti-KIR3DL2 mAb IPH4102 are now underway. In this review we discuss the various aspects of KIR3DL2 on the functions of CD4+ T cells and how targeting this receptor helps to develop innovative therapeutic strategies.